High rates of obesity and greater associated disability among people with rheumatoid arthritis in Canada. Issue 2 (February 2016) - Colmegna, Inés; Hitchon, Carol; Bardales, María; Puri, Lekha; Bartlett, Susan
Abstract Obesity in rheumatoid arthritis has been associated with increased risk of comorbidities, larger medical costs, decreased quality of life, higher disease activity, and reduced therapeutic responses. We assessed the burden of obesity among rheumatoid arthritis patients and its impact on patient-reported outcomes. Patients receiving care at two Canadian University Centers were included. Height and weight were measured and selected sociodemographic and rheumatoid arthritis (RA) characteristics as well as patient-reported outcomes were obtained. Patients were classified according to WHO criteria and proposed RA cut points, and results were compared with national data. Using WHO criteria, 68 (34 %) RA patients were classified as obese (vs. ~25 % of Canadians). Using RA cut points, 112 (55 %) RA patients were classified as obese. With both classification methods, obese individuals had significantly higher mean HAQ scores and a higher odds of significant disability (HAQ ≥ 1: WHO OR 2.3; 95 % CI 1.2, 4.2 and RA-specific OR 1.8; 95 % CI 1.0, 3.2). Independent of the classification method use, RA patients have significantly higher rates of obesity than national prevalence estimates. Obese RA patients had about twice the odds of reporting moderate to severe disability.